Inflamm-Aging and Brain Insulin Resistance: New Insights and Role of Life-style Strategies on Cognitive and Social Determinants in Aging and Neurodegeneration - Komleva, Yulia; Chernykh, Anatoly; Lopatina, Olga; Gorina, Yana; Lokteva, Irina; Salmina, Alla; Gollasch, Maik (Frontiers in Neuroscience, 2021)
Over the past decades, the human lifespan has dramatically increased, and therefore, a steady increase in diseases associated with age (such as Alzheimer's disease, Parkinson's disease) is expected. In these neurodegenerative diseases, there is a cognitive decline and memory loss, which accompanies increased systemic inflammation, the inflamm-aging, and the insulin resistance. Despite numerous studies of age-related pathologies, data on the contribution of brain insulin resistance, innate immunity components to aging are insufficient. Recently, much research has been focused on the consequences of nutrients, adiposity- and nutrients-related signals in brain aging and cognitive decline. Moreover, given the role of metainflammation in neurodegeneration, life-style interventions such as calorie restriction may be an effective way to break the vicious cycle of metainflammation and have a role in social behavior. The various effects of caloric restriction on metainflammation, insulin resistance, and neurodegeneration have been described. Less attention has been paid to the social determinants of aging and the possible mechanism by which caloric restriction might influence social behavior. The purpose of this review is to discuss current knowledge in interdisciplinary field of geroscience: immunosenescence, inflamm-aging and metainflammation, which make a significant contribution to aging. A substantial part of the review is devoted to frontiers in the brain insulin resistance in relation to neuroinflammation. In addition, we summarize new data on potential mechanisms of calorie restriction influence as a life-style intervention on social brain. This knowledge can be used to initiate successful aging and slow the onset of neurodegenerative diseases.